2017
DOI: 10.15376/biores.12.2.2421-2432
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of the Inhibition Effect of Model Compounds Representing Plant Biomass Degradation Products on Methane Production

Abstract: During the steam explosion pretreatment of plant biomass, degradation products are generated, and some of these have inhibitory activity against biogas production. The aim of this study was to investigate and quantify the effect of selected model inhibitory compounds on methane production. The results showed no significant inhibition of methane production by furfural at concentrations below 1 g/L. In addition, the microbial community was able to restore biogas production inhibited by this compound after a cert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The experimental data were used to derive basic parameters of the biodegradation curves with the help of a mathematical model adapted from [35]: Cco2=Cco2Max1+exp[2+4kCco2Max (Ct)]Cco2Max1+exp[2+4kCco2Max C] where CCO2Max is the maximal level of evolved CO 2 carbon expressed as the % of the maximal theoretical value; k represents the maximal rate of CO 2 production (days −1 ) and C is the length of the lag phase (days). The modeling was done in open source software Gnuplot (version 5.2, Thomas Williams, Colin Kelley).…”
Section: Methodsmentioning
confidence: 99%
“…The experimental data were used to derive basic parameters of the biodegradation curves with the help of a mathematical model adapted from [35]: Cco2=Cco2Max1+exp[2+4kCco2Max (Ct)]Cco2Max1+exp[2+4kCco2Max C] where CCO2Max is the maximal level of evolved CO 2 carbon expressed as the % of the maximal theoretical value; k represents the maximal rate of CO 2 production (days −1 ) and C is the length of the lag phase (days). The modeling was done in open source software Gnuplot (version 5.2, Thomas Williams, Colin Kelley).…”
Section: Methodsmentioning
confidence: 99%
“…In comparison to other publications, dealing with inhibitory effects of toxic compounds, an inhibition of the biogas process can probably be ruled out. As an example: Pekařová et al (2017) [11] reported an inhibitory effect only at a furfural concentration between 1-2 g/L by using sodium acetate as a carbon substrate. By contrast, concentrations below 1 g/L seemed to have a stimulating effect on methane production.…”
Section: Furfural Concentrations (Bmp)mentioning
confidence: 99%
“…One possible reason could be due to the fact that the microbial consortium involved in biogas production tends to have a higher tolerance to such inhibitory by-products (Monlau et al, 2014) [9]. For example, the treshold value for furfurals in biotechnological hydrogen production with single cultures is often given with 0.62 g/L (Siqueira and Reginatto, 2015) [10], whereas similar concentrations in biogas production generally lead to no negative effects (Pekařová et al, 2017) [11]. Further reasons could be due to lower substrate/inoculum and inhibitor/inoculum ratios as well as different incubation times (Monlau et al, 2014) [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, around 3600 mg/L of furfural was present in the condensate even after adsorption. According to [35], the furfural concentration at 2000 mg/L could inhibit the AD process and increases the lag phase. Further decrease in the furfural concentration could be possibly achieved through a sequential batch/column adsorption.…”
Section: Anaerobic Digestion Of Torrefaction Condensatementioning
confidence: 99%